Site reliability engineering : How Google runs production systems - Beyer, Betsy; Jones, Chris; Petoff, Jennifer; Murphy, Niall Richard (O'Reilly Media, 2016)
In this collection of essays and articles, key members of Google's Site Reliability Team explain how and why their commitment to the entire lifecycle has enabled the company to successfully build, deploy, monitor, and maintain some of the largest software systems in the world.